ETIKA KONSUMSI DALAM MENCAPAI FALAH - Ayu Pramesti, Shinta; Ihwanudin , Nandang (Moderation | Journal of Islamic Studies Review, 2021)
Consumption activities are part of a very important economic activity. Islamic studies of consumption are very important, so that someone is careful in using wealth or shopping. A country may have abundant wealth, but if the wealth is not regulated properly and the benefits are measured, then welfare will fail. To be able to implement the values of consumption in Islam, it is necessary to understand through the study of consumption ethics in an Islamic perspective. The writing method uses descriptive analysis and sources of writing using promer data sources taken through books, journals and other literature relevant to writing this scientific work. This paper offers about the ethics of consumption in Islam in accordance with the principles suggested in Islamic Sharia